Peranan Manager Opersional Dalam Meningkatkan Kinerja Karyawan di PT Pesat Jaya Persada Kabupaten Bogor - Yanti Hasbian Setiawati; Bakti Toni Endaryono; Muhammad Ades Priyanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2020)
The purpose of this study was to analyze and find out about the role of operational managers in improving employee performance at PT. Pesat Jaya Persada, Bogor Regency, including obstacles and efforts to improve employee performance. The method used in this study is a qualitative research that is by examining the perspective of participants with strategies that are interactive and flexible with sources and litersai in accordance with conditions in the field. The results of this study are the role of operational managers in improving employee performance at PT. Pesat Jaya Persada, Bogor Regency, by carrying out interrelated roles, roles related to information, and also the role in decision making. Interpersonal roles that consist of roles as figureheads, roles as leaders, and roles as intermediary officials. Roles related to information consist of a role as a monitor, a role as a disseminator, and a role as a spokesperson. The role as a decision maker consists of a role as an entrepreneur, a role as a distractor (disturbande handler), a role as a resource divisor (resource allocator), and a role as a negotiator. Training is needed on the company's management capabilities so that the quality of human resources is better in improving employee performance. The need for additional materials or infrastructure related to office operations both in the field of transportation or supporting equipment, there needs to be a relationship working procedures within the company and working procedures outside the company environment, so that it can decompose a clear and decisive job description.